Analisis Komprehensif Industri Gula Aren di Sulawesi Selatan - Samsi, Andi Nur; Hartini, Hartini (Pascasarjana Universitas Negeri Makassar, 2024)
This study examines community empowerment in palm sugar production in South Sulawesi, focusing on data up to 2023. The palm sugar industry holds significant economic potential but faces challenges such as limited human resources, capital, traditional equipment, and market access. The research aims to analyze the macroeconomic conditions of South Sulawesi, present production potential data, identify key challenges, evaluate empowerment programs, and formulate strategic recommendations.Using a literature review method, the study found that despite existing constraints, empowerment and innovation programs (such as the Tompobulu Palm Sugar Industry Center, Desa Bana's success in digital marketing, and Arentim's product innovation) have shown significant positive impacts on increasing production, income, and product diversification.In conclusion, to achieve sustainable growth and improve farmer welfare, a holistic strategy is needed, encompassing human resource capacity building, equipment modernization, product diversification, expansion of digital market access, strengthening policies, inter-stakeholder coordination, and continuous research and development.